(untitled) (Research, Society and Development, 2021)
Objective: to report the difficulties and benefits found in an interprofessional activity in a Basic Health Unit (UBS) located in a peripheral neighborhood of the capital of Pará. Methodology: this is a descriptive study with a qualitative approach, such as an experience report, which presents activities carried out by nursing and medical students in a UBS from April 2019 to March 2020. During this period, research activities were developed. interprofessional consultations with users, lectures and dynamics of health education and continuing education. Results: during participation, challenges were noted for the adoption of interprofessional practices, such as the resistance of health professionals and lack of physical space for practices. Among the benefits of these practices, there is an improvement in the process of building knowledge and an increase in the quality of care provided to the community. Conclusion: in this way, it is concluded that the Education through Work for Health Program is fundamental to change the scenario for an interprofessional context, consolidating the knowledge of students and professionals through collaborative practice in multiprofessional performance.